2005
DOI: 10.1101/gad.336305
|View full text |Cite
|
Sign up to set email alerts
|

Medial floor plate formation in zebrafish consists of two phases and requires trunk-derived Midkine-a

Abstract: The medial floor plate (MFP) is the ventral-most structure in the vertebrate neural tube with important organizer functions during specification and differentiation of neurons and glia. Its origin and the timing of the specification are matters of ongoing debates (see Strähle et al. 2004). In zebrafish, mutant analyses and lineage tracing have shown that MFP cells originate from a pool of midline precursor cells in the gastrula organizer, the embryonic shield (Appel et al. 1999;Le Douarin and Halpern 2000). Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 26 publications
0
33
0
Order By: Relevance
“…In contrast to this, we could show that the two duplicated midkine genes in zebrafish show divergent activities (Winkler et al, 2003). On one hand, Mdka regulates formation of the medial floor plate (Schafer et al, 2005). On the other hand, Mdkb is required for the formation of neural crest cells and sensory neurons (this study).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In contrast to this, we could show that the two duplicated midkine genes in zebrafish show divergent activities (Winkler et al, 2003). On one hand, Mdka regulates formation of the medial floor plate (Schafer et al, 2005). On the other hand, Mdkb is required for the formation of neural crest cells and sensory neurons (this study).…”
Section: Discussionmentioning
confidence: 61%
“…Zebrafish contains two duplicated midkine genes, mdka, and mdkb, with mostly nonoverlapping expression patterns and divergent activities during embryogenesis (Winkler et al, 2003). While Mdka functions in the formation of the medial floor plate in the ventral neural tube (Schafer et al, 2005), we have earlier shown that Mdkb is involved in neural plate patterning during gastrulation (Winkler and Moon, 2001). Using a dominant-negative approach, we initially reported that Mdkb is required for the formation of a subset of premigratory ncc expressing foxd3 (Winkler and Moon, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…To test for morpholino efficiency, a GFP-based approach was used as described earlier (50). Briefly, the 25-nucleotide target sequence for the mc2r morpholino was cloned in front of GFP into the CS2ϩGFP expression vector using annealed oligos containing BamHI overhangs.…”
Section: Morpholino Injectionmentioning
confidence: 99%
“…33,34 In a recent study in zebra fish, which have two species of MK due to gene duplication, it was established that a form of MK plays essential roles in the formation of the medial floor plate, one of the most ventral neural tube structures. 35 The factors are also expressed in specific regions during development of the sensory organs, suggesting roles in the developmental process. 20,21 MK and PTN have 45% sequence identity at the protein level, and share many of the in vitro activities.…”
mentioning
confidence: 99%